International Labour Force Participation Rates by Gender: Unit Root or Structural Breaks? - Zeynel Abidin Ozdemir; Mehmet Balcilar; Aysit Tansel (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
This paper examines the possibility of unit roots in the presence of endogenously determined multiple structural breaks in the total, female and male labour force participation rates (LFPR) for Australia, Canada and the USA. We extend the procedure of Gil-Alana (2008) for single structural break to the case of multiple structural breaks at endogenously determined dates using the principles suggested by Bai and Perron (1998). We use the Robinson (1994) LM test to determine the fractional order of integration. We find that endogenously determined structural breaks render the total, female and male LFPR series stationary or at best mean-reverting.
Keywords: C22; E24; J16; J21; 330; Labour Force Participation Rates; Gender; Fractional Integration; Structural Breaks; Erwerbstätigkeit; Geschlecht; Einheitswurzeltest; Strukturbruch; Schätzung; Australien; Kanada; USA